Generation of albino medaka (Oryzias latipes) by CRISPR/Cas9. Issue 4 (5th June 2018) - Fang, Jian; Chen, Tiansheng; Pan, Qihua; Wang, Qian
Abstract: CRISPR/Cas9 system is a powerful tool to produce the genetic modification in plants and animals such as mouse and zebrafish. However, this technique was less reported in fish model medaka ( Oryzias latipes ). Here, we describe an efficient and rapid procedure for genome editing in medaka tyr and generate a stable albino strain. The Cas9 mRNA and gRNA for tyr gene were injected into the embryos of orange‐red medaka, and the tyr gene was disrupted in more than 90% of embryos in F0 and F1, which were validated by observation and sequencing of targeted locus. The pigment cells were largely decreased in the mutant medaka because open reading frames of tyr were shifted near the targeted locus, generating albino medaka. Taken together, this method provides a detailed procedure to generate the genetic modification medaka by using an optimized CRISPR/Cas9 system, and the new albino medaka provides an important research platform to study the pigmentation. GRAPHICAL ABSTRACT: Established an efficient and rapid procedure for genome editing in medaka tyr Generated stable albino strains